Functional polymorphisms of NOS3 and GUCY1A3 affect both nitric oxide formation and association with hypertensive disorders of pregnancy - Pereira, Daniela A.; Luizon, Marcelo R.; Palei, Ana C.; Tanus-Santos, José E.; Cavalli, Ricardo C.; Sandrim, Valeria C. (Frontiers in Genetics, 2024)
Impaired nitric oxide (NO) formation may be associated with endothelial dysfunction and increased cardiovascular disease risk in preeclampsia (PE). Functional SNPs of NOS3 (rs3918226) and GUCY1A3 (rs7692387) increase susceptibility to the adverse consequences of inadequate generation of NO by endothelium. However, no previous study has examined whether these SNPs affect NO formation in healthy pregnancy and in gestational hypertension (GH) and PE. Here, we compared alleles and genotypes of NOS3 (rs3918226) and GUCY1A3 (rs7692387) SNPs in normotensive pregnant women (NP, n=153), in GH (n=96) and PE (n=163), and examined whether these SNPs affect plasma nitrite concentrations (a marker of NO formation) in these groups. We further examined whether the interaction among SNP genotypes is associated with GH and PE. Genotypes were determined by Taqman allele discrimination assays, and plasma nitrite concentrations by an ozonebased chemiluminescence assay. Multifactor dimensionality reduction was used to examine interactions among SNP genotypes. Regarding NOS3 rs3918226, the CT genotype (p=0.046) and T allele (p=0.020) were more frequent in NP than GH, and GH patients carrying the CT+TT genotypes showed lower nitrite concentrations than NP carrying the CT+TT genotypes (p<0.05). Regarding GUCY1A3 rs7692387, the GA genotype (p=0.013) and A allele (p=0.016) were more frequent in PE than NP, and NP carrying the GG genotype showed higher nitrite concentrations than GH or PE patients carrying the GG genotype (p<0.05). However, we found no significant interactions among genotypes for these functional SNPs to be associated with GH or PE. Our novel findings suggest that NOS3 rs3918226 and GUCY1A3 rs7692387...